Predicting power consumption in continuous oscillatory baffled reactors. (2nd February 2020) - Avila, M.; Fletcher, D.F.; Poux, M.; Xuereb, C.; Aubin, J.
Graphical abstract: Highlights: Use of the mechanical energy equation gives better estimate of power dissipation. Net flow has a non-negligible influence on power density at low velocity ratios. Empirical models for power density are still not valid for all operating conditions. Dimensionless power curve is a useful design tool for predicting power density. Abstract: Continuous oscillatory baffled reactors (COBRs) have been proven to intensify processes, use less energy and produce fewer wastes compared with stirred tanks. Prediction of power consumption in these devices has been based on simplistic models developed for pulsed columns with single orifice baffles several decades ago and are limited to certain flow conditions. This work explores the validity of existing models to estimate power consumption in a COBR using CFD simulation to analyse power density as a function of operating conditions (covering a range of net flow and oscillatory Reynolds numbers: Re net = 6 - 27 / Re o = 24 - 96 ) in a COBR with a single orifice baffle geometry. Comparison of computed power dissipation with that predicted by the empirical quasi-steady flow models shows that this model is not able to predict correctly the values when the flow is not fully turbulent, which is common when operating COBRs. It has been demonstrated that dimensionless power density is inversely proportional to the total flow Reynolds number in laminar flow and constant in turbulent flow, as is the case for flow in pipes and stirred tanks. For the geometry studied here P / V ∗ = 330 / Re T in laminar flow and P / V ∗ = 1.92 in turbulent flow.